Responsabilidad social empresarial como herramienta de evaluación según la norma ISO 14001 en la empresa municipal de agua potable y alcantarillado de Guaranda “E-P EMAPA-G”, año 2023 - Chimbolema Chimbo, Erika Sandra (2025)
The Corporate Social Responsibility (CSR) as an evaluation tool according to the ISO 14001 standard in the Municipal Drinking Water and Sewage Company of Guaranda (E-P EMAPA-G), analyzes the integration of CSR within the framework of the environmental management system based on the ISO 14001 standard. The research seeks to identify how CSR can improve the company's environmental management and contribute to compliance with regulatory requirements and operational sustainability. Through a mixed methodological approach, data were collected through interviews, surveys in the company. The results show that the implementation of CSR practices allows for more efficient environmental management, increases environmental awareness among employees and improves the relationship with the local community. Likewise, the need for a model that fully integrates CSR into the environmental management system is highlighted. Finally, specific recommendations are proposed for the E-P EMAPA-G in the implementation of CSR as a tool for continuous improvement, aligned with the objectives of ISO 14001, guaranteeing the sustainable development of its operations.